Lean thinking in healthcare phlebotomy services: a case study - Simões, Natacha Maria Vinhas (2017)
Lean Thinking arises as a solution to address the rising costs of healthcare. This dissertation aims to evaluate the potential of applying Lean tools to healthcare phlebotomy services. Furthermore, a theoretical framework is provided in order to support the present research. Case study’s methodology is applied to the phlebotomy service of a private and a public hospital of Lisbon where direct observation and informal interviews are performed to internal and external customers. Value stream mapping, process activity mapping, spaghetti diagram and time value map are applied to the core process of a phlebotomy service: blood collection. Healthcare customers are identified and their perception of value is revealed. Waste is identified using the selected tool, recognised in the methodology, and improvement suggestions are proposed. The outcome of this research shows that the application of Lean thinking can convey possible gains to healthcare phlebotomy services if improvement suggestions are implemented, as the process would become more precise and reduce the total cycle time benefiting internal and external customers, increasing process efficiency. Considering the elimination of waste in the blood collection process, median total time’s reduction is expected to be by 47% for Lusíadas Hospital and 37% for São Francisco Xavier Hospital, in addition to reducing the median wasteful time by 54% and 46%, respectively, and the reduction of the distance covered by phlebotomists, receptionists and technical staff involved.